Flow control by using an IBM/PC / Jemat Salleh and Suhaimi Che Mustapha - Salleh, Jemat; Che Mustapha, Suhaimi (1990)
This project is an example of a simple discrete computer control without feedback. The appropriate valves and haeters are turned on and off according to the programmed instruction. The 8255 Chip (Programmable Input/Output Function) is used to interface the computer and the process and we use delay to set the time for the valves to open or close. There are six output signal from port A and they are used to control the six variables in the process.